A Direct Aspiration First Pass Technique in Japanese Real-World Clinical Setting. Issue 2 (28th November 2018) - Uno, Junji; Kameda, Katsuharu; Otsuji, Ryosuke; Ren, Nice; Nagaoka, Shintaro; Maeda, Kazushi; Ikai, Yoshiaki; Gi, Hidefuku
Abstract: BACKGROUND: It is debatable whether mechanical thrombectomy has benefits in a real-world setting outside the more rigid and selective clinical trial environment. OBJECTIVE: To evaluate clinical outcomes, efficacy, and safety of mechanical thrombectomy in single-center retrospective cohort case series. METHODS: We reviewed prospectively collected data from our large-vessel occlusion stroke database to identify patients undergoing mechanical thrombectomy using Penumbra catheters (Penumbra, Almeida, California) as first-line devices. The primary outcomes were the modified Rankin Scale score at 90 d and recanalization rate. The secondary outcomes included the rates of hemorrhagic complications and mortality. RESULTS: The entire study population included 298 patients. Thrombolysis in Cerebral Infarction Scale ≥2b was achieved in 86.6% of patients. Fifty-five patients (18.5%) were outside the 6 hr time window and 82 patients (27.5%) were over 80-yr old. The posterior circulation thrombectomy rate was 12.4%. At 90 d from onset, 49.3% of patients had favorable outcomes. The parenchymal hemorrhage type 2 (PH2) and subarachnoid hemorrhage rates were 2.3% and 11.7%, respectively. In multivariate analyses, cerebral blood flow/cerebral blood volume mismatch (odds ratio [OR] = 9.418; 95% confidence interval [CI], 3.680-27.726; P < .0001), onset to recanalization time (OR = 0.995; 95% CI, 0.991-0.998; P = .0003), and hemorrhagic complications including PH2 and subarachnoid hemorrhage (OR = 0.186; 95% CI, 0.070-0.455; P = .0002) were associated with favorable outcomes. CONCLUSION: A direct aspiration first pass technique with an adjunctive device demonstrated high recanalization rates in old Japanese patients. Our patient cohort may reflect the application of endovascular techniques in acute ischemic stroke treatment in a real-world setting.